Vita sotto le armi, vita clandestina Cronaca e silenzio nei diari di un ufficiale (1940-1943) - Ricciardi, Elisabetta (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2010)
The diaries of the cavalry lieutenant Carlo Ricciardi (1916-1966) record personal events and impressions of the Second World War in Italy, Yugoslavia and Russia. They bring clearly to the fore the logistic difficulties encountered at the front, the clashes with the Croatian and German allies and the drama of the Russian defeat at the beginning of 1943. The commentary of the diaries is supplemented by a study on the role of soldiers in the resistance, of which Ricciardi was one of the protagonists in Lombardy. Analysis of a vast documentation, partly original, casts a new light on the resistance organisations in the North, on the close collaboration between partisans, the Finance police and the clandestine information services from the armistice up to the negotiations for the German surrender in Italy.